INNOVATION OF LOCAL GOVERNMENT AND PRIVATE PARTNERSHIP PROGRAMS IN EMPOWERING COMMUNITIES AFFECTED BY COVID-19 IN BATURAJA TIMUR DISTRICT, OGAN KOMERING ULU REGENCY - Eva Susanti; Aprilia Lestari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
A pandemic situation like the one faced some time ago has caused part of the community's economy to decline. Therefore, the government and the private sector are always trying to explore various innovations in increasing the economic capacity of the community in the midst of a pandemic. The Baturaja People's Credit Bank (BPR Baturaja) together with the regional government of Ogan Komering Ulu Regency, in this case the Department of Trade and MSMEs, are partners in implementing community empowerment programs affected by the co-19 pandemic. The purpose of this study was to determine the partnership between the government and the private sector in carrying out innovative community empowerment programs, and to measure the success of the empowerment programs carried out. More specifically, this research is intended to determine the strengths and weaknesses of the program being implemented, so as to produce recommendations to strengthen the program. This study uses a qualitative research method, in order to examine in depth about public-private partnerships, which is not possible to study quantitatively. Based on research, the community empowerment program carried out by a government-private partnership in the Ogan Komering Ulu district was realized in the form of a program providing catfish seeds and a set of equipment for communities affected by Covid-19. In this empowerment program, the local government acts as a decision maker, target setter, facilitator in linking the community with the private sector, and as a supervisor in program implementation. Meanwhile, the private sector (BPR Baturaja) acts as a provider of capital and oversees the implementation of the program.